THE EFFECT OF STUDENTS SOCIAL INTERACTION ON THEIR LEARNING MOTIVATION DURING DISTANCE LEARNING TO MODELING AND BUILDING INFORMATION DESIGN PROGRAM (MBID) STUDENTS AT PUBLIC VOCATIONAL HIGH SCHOOL (PVHS) IN BANDUNG - Intan Salamah Nur Islami; Rr Tjahyani Busono; Riskha Mardiana (Universitas Pendidikan Indonesia, 2022)
Thesis with the title “The Effect of Students Social Interaction on Their Learning Motivation During Distance Learning to Modeling and Building Information Design Program (MBID) Students at Public Vocational High School (PVHS) in Bandung” is a research during distance learning that observe about students social interaction and their learning motivation in case of MBID program students at PVHS in Bandung. Distance learning performs with online and offline learning that be adapted by government regulations of pandemic learning situation. Its impact the change of social interaction on learning process as online learning from home and offline learning at school with Covid-19 protocol. This change is during distance learning involve students interaction would change with their teachers, their parents, and the other students. It can affect the students learning motivation, to their intrinsic and extrinsic motivation. This thesis is using quantitative method by questionnaire spread with likert scale, it’s analyzed with compare means and simple regression analysis. The result is indicate the students social interaction and their learning motivation in a good category with each means score 3.75 and 3.76, it also points there is effect of students social interaction on their learning motivation with the value until 63.7%.